Pengembangan Pemasaran Makanan Khas Kipang untuk Meningkatkan Pendapatan (Studi Kasus Kipang Pulut Bonjol Ita) - Aulia Putri Utami; Ali Rahman (ARZUSIN, 2026)
MSME marketing strategies have received attention in various previous studies, but studies that specifically discuss the integration of conventional and digital marketing in increasing the income of traditional culinary businesses remain limited. This study aimed to analyze the marketing strategies implemented and their contribution to increasing income in the Kipang Pulut Bonjol Ita business. This study used a qualitative approach with a case study design, involving main and supporting informants selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using interactive analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that the marketing strategies implemented were still dominated by conventional approaches, particularly in the aspects of distribution and promotion. Distribution expansion was proven to contribute to increasing sales volume and business income, while the use of social media in promotion was able to increase product exposure, although it had not been optimally utilized. This finding contributes to the development of marketing mix studies, particularly in the aspects of distribution and promotion in the context of traditional culinary MSMEs, and expands understanding of the importance of integrating conventional and digital marketing strategies. Thus, distribution strategy is an important factor in expanding market reach and increasing business income, while digital marketing optimization is needed to strengthen the competitiveness of traditional culinary MSMEs.